The Attitude of Muslim Scientists in Facing Technological Progress and Their Responsibility Towards Nature and the Environment - Oihana Febby Iswantoro; Dinan Fadila Ihwan; Didik Himmawan (Aslama: Journal of Islamic Studies, 2025)
This article discusses the attitudes of Muslim scientists in facing technological advances and their responsibilities towards nature and the environment. Currently, the Industrial Revolution 4.0 has created a phenomenon in the business world called disruptive innovation, which is an innovation that creates new habits and new industrial networks, which ultimately "disrupt" the market and values ​​that already exist, then replace the "old players" to become market leaders and then make alliances in it (Bower & Christensen, 1995). Learning Islamic Religious Education with internet technology makes students more active, students can interact directly with fellow learners, as well as with experts in their fields. The learning process is not limited by the classroom, the role of the teacher as a facilitator, learning resources can come from anywhere, and learning becomes a process of analyzing the information obtained. This certainly affects not only the teaching and learning process in the classroom, but also the entire education system through the use of management information systems in schools. The research method used in this design is a qualitative method with a literature study approach, in the technique of reviewing and concluding various literature sources that are relevant to the topic of the article being discussed. Literature study also means data collection techniques by reviewing books, literature, notes, and various reports related to the problem to be solved. The results of this article are that Muslims have contributed to the development of technology that facilitates daily activities, including facilitating Muslim worship. The following are some technological innovations that have been developed by Muslims, the responsibility of Muslim scientists towards nature and the environment as humans has two functions, namely as abdun (servants of Allah) and as Allah's caliph on earth, as caliph (representative of Allah) on earth. Muslim scientists have a great responsibility towards preserving nature and the environment as part of their role as caliphs on earth.